Comprehensive Guidance and Counseling Programs in Developing Student Talent - Lestari, Lestari; Izzaty, Rita Eka (Universitas Mercu Buana Yogyakarta, 2020)
This article provides an overview of multicultural competencies from a global perspective, specifically as it relates to counseling students in Indonesia. An overview will be given of the cultural interactions observed by counselor educators who were visiting professors at a university in Indonesia. While racial and ethnic diversity in countries such as Indonesia remain homogenous, cultural differences were noted with respect to the intersectionality of gender and disability. The intersection of culture, gender, and disability present unique challenges for counselors trying to assist their clients. Thus, it is imperative that counseling students become culturally competent so they can assist their clients who come from varying backgrounds. Implications are given to counseling programs to increase their students’ multicultural competencies when working with global populations.